2020
DOI: 10.1038/s41467-020-19619-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 structure and replication characterized by in situ cryo-electron tomography

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the COVID19 pandemic, is a highly pathogenic β-coronavirus. As other coronaviruses, SARS-CoV-2 is enveloped, replicates in the cytoplasm and assembles at intracellular membranes. Here, we structurally characterize the viral replication compartment and report critical insights into the budding mechanism of the virus, and the structure of extracellular virions close to their native state by in situ cryo-electron tomography and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

59
684
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(799 citation statements)
references
References 57 publications
59
684
2
2
Order By: Relevance
“…We envision two possible modes of N protein tetramer assembly based on either parallel or antiparallel arrangement of the putative α‐helices in the N3 domain (Figure 3h). How these tetramers interact with viral RNA and self‐assemble into either helical filaments or the more recently observed globular viral RNP complexes 29 will require higher‐level reconstitution and/or high‐resolution analysis of the internal structure of SARS‐CoV‐2 virions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We envision two possible modes of N protein tetramer assembly based on either parallel or antiparallel arrangement of the putative α‐helices in the N3 domain (Figure 3h). How these tetramers interact with viral RNA and self‐assemble into either helical filaments or the more recently observed globular viral RNP complexes 29 will require higher‐level reconstitution and/or high‐resolution analysis of the internal structure of SARS‐CoV‐2 virions.…”
Section: Discussionmentioning
confidence: 99%
“…One critical step in coronavirus replication is the assembly of the viral genomic RNA and nucleocapsid (N) protein into a ribonucleoprotein (RNP) complex, which interacts with the membrane (M) protein and is packaged into virions. Electron microscopy analysis of related betacoronaviruses has suggested that the RNP complex adopts a helical filament structure, 23–28 but recent cryoelectron tomography analysis of intact SARS‐CoV‐2 virions has revealed a beads‐on‐a‐string like arrangement of globular RNP complexes that sometimes assemble into stacks resembling helical filaments 29 . Despite its location within the viral particle rather than on its surface, patients infected with SARS‐CoV‐2 show higher and earlier antibody responses to the nucleocapsid protein than to the surface spike protein 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…These C-terminal residues are unresolved in the cryo-EM structures of the spike trimer, 3 , 7 and it has been suggested that they have extensive conformational flexibility based on electron microscopy of soluble trimers and viral particles. 41 43 Additionally, this region of the spike contains an immunodominant linear epitope, as determined via analysis of convalescent sera from COVID-19 patients. 44 , 45 We therefore hypothesized that deleting these residues would more readily facilitate formation of spike ferritin particles and could influence immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the particular implications of these proteins during SARS-CoV-2 assembly needs further investigation. Viral budding of other coronaviruses occurs through the ER-Golgi exocytosis pathway [ 72 , 73 ], and preliminary data suggests that this might also be the case for SARS-CoV-2 [ 74 ]. The host factor CD74 can block the activity of cathepsins and is expressed in the ER membranes of immune cells, where it facilitates the export of MHC-II from the ER towards vesicles that fuse with the late endosome.…”
Section: Ebov Egress and Common Gateways To Sars-cov-2mentioning
confidence: 99%